POS0302 TREAT-TO-TARGET IN SPONDYLOARTHRITIS (SPA): ARE THERE SEX-RELATED DIFFERENTIAL RESPONSES? - Yip, C.C.Y.; Cheng, I.T.; So, H.; Leung, Y.Y.; Shin, K.; Saeed, M.A.; Subramanian, N.; Chiowchanwisawakit, P.; Chung, H.Y.; Kishimoto, M.; Wei, J.C.C.; Tam, L.S. (Annals of the rheumatic diseases, 2023)
Studies have reported that female patients with spondyloarthritis (SpA) have different disease courses and treatment responses compared to male patients. Whether patients' sex, the biological attributes associated with being male or female, is associated with a different outcome after receiving one-year of tight control, treat-to-target (T2T) strategy remain uncertain. This study aimed to evaluate the differences in the clinical response between male and female patients from the Asia Pacific League of Associations for Rheumatology (APLAR) SpA Registry. Patients who fulfilled the CASPAR 2006 classification criteria for psoriatic arthritis (PsA) and 2009 ASAS classification for axial spondylitis (AxSpA) were recruited. They received 1 year of protocolized treatment aiming at 1) minimal disease activity (MDA) or Disease Activity in Psoriatic Arthritis (DAPSA) low disease activity (LDA) for PsA patients, and 2) Ankylosing Spondylitis Disease Activity Score (ASDAS) LDA for AxSpA patients. Patients were assessed every 3 monthly and treatment was escalated if target was not reached. 63 male (age: 45±15 years, 27 PsA, 36 AxSpA) and 36 female (age: 46±12 years, 22 PsA, 14 AxSpA) subjects from 6 Asia-Pacific regions were included. At baseline, male had more tender joints but less severe enthesitis than female. Male AxSpA patients had a lower Bath Ankylosing Spondylitis Disease Activity Index (BASDAI) but male PsA patients had a higher DAPSA. Other baseline characteristics were shown in Table 1. During the study period, the use of conventional synthetic disease-modifying anti-rheumatic drugs (csDMARDs) decreased slightly, while the use of biologics (bDMARDs) significantly increased across both sexes (Figure 1). After 1-year treatment, there were significant improvements in disease activity in the entire cohort (DAPSA: 15.3±11.6 at baseline vs 10.1±11.2 at 1-year, p=0.002; ASDAS: 2.4±1.0 at baseline vs 1.9±0.9 at 1-year, p=0.003). Despite having lower CRP levels (2.3 ± 2.5mg/L in female vs 8.7±17.7mg/L in male, p=0.008) and higher bDMARDs use in female patients (54% in female vs 45% in male) at 1-year, their clinical responses were less optimal compared to male patients. Female patients had a higher patients' global assessment score (3.9±2.4 in female vs 2.9±2.2 in male, p=0.035). Disease activity in female PsA patients and the number of tender joint count in both PsA and AxSpA increased while that in male patients improved (% change in DAPSA: -47% in male vs +19% in female, p=0.003); % change in tender joint count: -70% in male vs +19% in female, p=0.014). Both patients' and physicians' global assessment scores increased in female SpA patients whilst that in male SpA patients decreased. There was also a trend showing less improvement in other parameters in female patients (Figure 1). [Display omitted] There may be differential treat-to-target responses between male and female SpA patients. The causes of such differential characteristics should be further explored to potentially implement a sex-specific treat-to-target strategy for spondyloarthritis. NIL. NIL. Carson C.Y. Yip: None declared, Isaac T. Cheng: None declared, Ho So: None declared, Ying Ying Leung: None declared, Kichul Shin: None declared, Muhammad Ahmed Saeed: None declared, Nallasivan Subramanian: None declared, Praveena Chiowchanwisawakit: None declared, Ho Yin Chung: None declared, Mitsumasa Kishimoto Consultant of: AbbVie, Amgen, Asahi-Kasei Pharma, Astellas, Ayumi Pharma, BMS, Celgene, Chugai, Daiichi-Sankyo, Eisai, Eli Lilly, Gilead, Janssen, Kyowa Kirin, Novartis, Ono Pharma, Pfizer, Tanabe-Mitsubishi, and UCB Pharma, James Cheng-Chung Wei Consultant of: Tsh biopharm, Abbvie, BMS, Celgene, Chugai, Eisai, Janssen, Novartis, Pfizer, Sanofi-Aventis and UCB pharma, Grant/research support from: Abbvie, Amgen, Astellas, BMS, Celgene, Eli Lilly, Gilead, Janssen, Novartis, Pfizer Sun and UCB, Lai-Shan Tam: None declared. Table 1Demographics, clinical features and disease activity in patients with Spondyloarthritis in APLAR region at baseline, stratified by genderMale (n=63)Female (n=36)pAge, years45±1546±12Presence of sacroiliitis in Xray13597%857%*NRS Patients' pain assessment, 0-103.9±2.24.3±2.2NRS Patients' global assessment, 0-103.9±2.34.3±2.0NRS Physicians' global assessment, 0-103.5±2.33.4±2.0TJ count, 0-682.8±5.31.0±1.3*SJ count, 0-661.5±3.40.7±1.3Dactylitis digits0.3±1.40.1±0.4PASI23.56±5.841.68±2.58SPRACC, 0-150±11±1*ESR, mm/h20±1827±22CRP, mg/L18.0±55.67.5±10.2MDA achieved2829.6%949.9%DAPSA217.57±13.5710.40±5.76*ASDAS CRP12.29±1.002.90±0.93BASDAI13.0±1.85.1±2.4*BASFI12.2±1.94.5±2.5*BASMI13±22±1*HAQ-DI0.395±0.4930.622±0.574*1For Axial SpA only, 2for PsA only.